Acceptability of a High-Calcium Prebiotic Food Formula Made from Chicken Feet, Garlic, and Banana for Stunted Children - Dinda Novianti; Edy Waliyo; Iman Jaladri (MEDICA (International Medical Scientific Journal), 2023)
Stunting, or short stature, is a condition in which a person's height is not appropriate for their age. Adequate intake of both macronutrients and micronutrients is essential to prevent or reduce the risk of stunting. In addition to calcium-rich foods, the inclusion of prebiotic-containing foods is highly recommended. To ensure the intake of both calcium and prebiotics, a food formula composed of chicken feet bones, bananas, and garlic—referred to as a calcium-prebiotic food formula—was developed. The composition of the formula was based on the CODEX STAN 181-1991 standard, with an energy content of approximately 200–400 kcal to support weight management. This study aimed to evaluate the acceptability of the calcium-prebiotic food formula made from chicken feet, garlic, and bananas for children with stunting. This study used an experimental design consisting of three formulations: F1 (75%:25%), F2 (50%:50%), and F3 (25%:75%). Organoleptic tests were conducted using a panel to assess acceptability in terms of color, aroma, texture, and taste. The Friedman statistical test showed no significant differences among the three formulations in terms of color, aroma, texture, and taste. It is recommended that further laboratory testing be conducted to determine the protein and calcium content for more accurate nutritional profiling.